Improved diagnosis of antibiotic-associated haemorrhagic colitis (AAHC) in faecal specimens by a new qualitative real-time PCR assay detecting relevant toxin genes of Klebsiella oxytoca sensu lato. (May 2022) - Leitner, Eva; Bozic, Michael; Kienesberger, Sabine; Cosic, Amar; Landt, Olfert; Högenauer, Christoph; Kessler, Harald H.
Abstract: Objective: Toxin-producing Klebsiella oxytoca causes antibiotic-associated haemorrhagic colitis (AAHC). The disease-relevant cytotoxins tilivalline and tilimycine produced by certain K. oxytoca isolates are encoded by the non-ribosomal peptide synthetase genes A ( npsA ) and B ( npsB ). In this study, the new LightMix® Modular kit for the detection of relevant K. oxytoca sensu lato (s.l.) toxin genes was evaluated. Methods: DNA was extracted on the automated EMAG® platform. Amplification was done on the Light Cycler® 480 II instrument. In total, 130 residual faecal specimens collected from patients with antibiotic-associated diarrhoea were studied to determine the clinical sensitivity and specificity. Toxigenic culture served as reference method. Results: With the new kit, the limit of detection was 15 CFU/mL for all targets. For the pehX target specific to K. oxytoca s.l., 65 of 130 clinical specimens were positive, while toxin-specific targets ( npsA / npsB ) were positive in 47 of 130. The npsA / npsB PCR targets showed a clinical sensitivity of 100% (95%CI 80.5–100%) and a specificity of 73.5% (95%CI 64.3–81.3%) with a positive predictive value of 16.5% (95%CI 12.7–21.2%) and a negative predictive value of 100%. Conclusion: Compared with culture, additional clinical specimens positive for K. oxytoca s.l. were detected with real-time PCR. The specificity of the toxin targets appears moderate due to the inferior sensitivity of the culture-based reference method. Since the developed assay is highly sensitive, it may be used as first-line method to improve the diagnosis of AAHC.